Struktur dan Makna Puisi “Ibu” Karya Chairil Anwar: Kajian Struktural dalam Pengajaran Sastra - Rahmadi Rahmadi; Dwi Wahyu Candra Dewi (BADAN PENERBIT STIEPARI PRESS, 2025)
Poetry, as a medium of aesthetic and reflective expression, holds significant potential in developing students' critical literacy. However, the complexity of form and symbolism in poetry often becomes a barrier in the learning process. This study aims to analyze the poem Ibu by Chairil Anwar using a structural approach to reveal the interrelation between physical and inner structures in constructing meaning, as well as to examine its relevance in literature learning at the secondary school level. Employing a Qualitative descriptive-analytical method, this study explores the poem’s physical structure such as typography, diction, imagery, and figures of speech and its inner structure, including theme and message. The analysis reveals that the poem Ibu is composed with simplicity yet conveys deep emotional and spiritual layers, reflecting profound reverence toward the mother figure. The structural approach proves effective in systematically uncovering meaning and is applicable in classroom settings, supporting the integration of analytical and contextual literary education aligned with the Merdeka Curriculum. These findings underscore the urgency of implementing structural analysis as a pedagogical strategy to enhance literary appreciation and critical literacy in secondary education.